LGR6 modulates intervertebral disc degeneration through regulation of macrophage efferocytosis - Li, Fudong; Shi, Yangyang; Chen, Jun; Sun, Jingchuan; Shi, Jiangang; Sun, Kaiqiang; Zheng, Bing (Journal of translational medicine, 2025)
Intervertebral disc degeneration (IVDD) is a leading cause of chronic low back pain, characterized by extracellular matrix (ECM) degradation, excessive inflammation activation, and increased cell apoptosis. LGR6, a receptor known for its role in tissue regeneration, has recently been implicated in modulating macrophage efferocytosis, a process critical for clearing apoptotic cells and maintaining tissue homeostasis. This study aimed to investigate the role of LGR6 in regulating IVDD progression and to focus on its impact on macrophage efferocytosis, ECM regulation, and apoptosis in nucleus pulposus cells (NPCs). A comprehensive bioinformatic analysis was performed using datasets GSE56081 and GSE70362 to identify differentially expressed genes (DEGs) and gene modules associated with IVDD. Principal component analysis (PCA), volcano plots, and hierarchical clustering were utilized to assess gene expression patterns. Weighted Gene Co-Expression Network Analysis (WGCNA) was employed to identify gene modules correlated with IVDD, and integrative analysis pinpointed key genes and pathways. In vitro, LGR6 expression in macrophages was manipulated through shRNA interference and overexpression assay. The effects of LGR6 on macrophage efferocytosis, ECM synthesis, and apoptosis were assessed. An in vivo IVDD model was established in mice via disc puncture to evaluate the impact of LGR6 modulation on disc degeneration. Bioinformatic analysis revealed distinct gene expression profiles between control and IVDD samples, with key gene modules identified by WGCNA showing strong correlations with IVDD. Integrative analysis highlighted critical pathways, including ECM-receptor interaction and efferocytosis, that are potentially regulated by several key genes including SERPINA1, THBS4, ELMO1, LGR6, and ITGB8. Of those genes, LGR6 appeared to be the gene most closely related to IVDD severity. In addition, the mRNA level and protein level of LGR6 in macrophages co-cultured with IL-1β-treated NPCs were raised significantly, compared to the control group. In vitro, LGR6 overexpression enhanced macrophage efferocytosis. Meanwhile, under co-culturing with IL-1β-treated NPCs, LGR6 overexpression in macrophages led to increased expression of ECM components such as COL2A1 and decreased expression of matrix-degrading enzymes like MMP13, indicating a protective effect against matrix degradation. Additionally, LGR6 overexpression inhibited IL-1β-induced apoptosis in NPCs by upregulating anti-apoptotic proteins (BCL2) and downregulating pro-apoptotic markers (cleaved caspase 3 and BAX). Conversely, LGR6 knockdown impaired macrophage efferocytosis and exacerbated NPCs apoptosis. In the mouse IVDD model, promoting efferocytosis resulted in improved ECM integrity and reduced apoptosis; and suppressing efferocytosis caused opposite effect, further supporting the protective role of LGR6-related efferocytosis in IVDD. LGR6 significantly contributes to the protective effects on IVDD by modulating macrophage efferocytosis, enhancing ECM synthesis, and reducing apoptosis in NPCs. These findings highlight that LGR6 could be a promising therapeutic target for IVDD, with its dual role in regulating immune responses and preserving tissue integrity. Future studies are necessary to evaluate the clinical potential of LGR6-based therapies in treating degenerative disc diseases.